2018
DOI: 10.1038/s41419-018-1205-6
|View full text |Cite
|
Sign up to set email alerts
|

p73 regulates ependymal planar cell polarity by modulating actin and microtubule cytoskeleton

Abstract: Planar cell polarity (PCP) and intercellular junctional complexes establish tissue structure and coordinated behaviors across epithelial sheets. In multiciliated ependymal cells, rotational and translational PCP coordinate cilia beating and direct cerebrospinal fluid circulation. Thus, PCP disruption results in ciliopathies and hydrocephalus. PCP establishment depends on the polarization of cytoskeleton and requires the asymmetric localization of core and global regulatory modules, including membrane proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 62 publications
2
45
0
1
Order By: Relevance
“…Interestingly, it was suggested that p73 marks some basal cells in airway epithelium for MCC differentiation, lending to it a role as a pioneer or competence factor [8]. Further supporting the importance of p73, it was also reported that it regulates ependymal MCC polarity through maintenance of actin and microtubule cytoskeletal networks [10]. It is important to mention that the MCC identity is inherently labile, as its maintenance requires constant FoxJ1 transcriptional activity, at least in murine ependymal MCCs [11].…”
Section: Establishment and Maintenance Of MCC Identitymentioning
confidence: 91%
“…Interestingly, it was suggested that p73 marks some basal cells in airway epithelium for MCC differentiation, lending to it a role as a pioneer or competence factor [8]. Further supporting the importance of p73, it was also reported that it regulates ependymal MCC polarity through maintenance of actin and microtubule cytoskeletal networks [10]. It is important to mention that the MCC identity is inherently labile, as its maintenance requires constant FoxJ1 transcriptional activity, at least in murine ependymal MCCs [11].…”
Section: Establishment and Maintenance Of MCC Identitymentioning
confidence: 91%
“…Mechanistically, TAp73 regulates translational PCP (asymmetrical polarization of cilia clusters at the anterior apical surface) by directly inducing transcription of Mlck kinase (also known as Mylk), which modulates non-muscle myosin-II activity, thereby affecting the dynamics of actin and microtubulebased transport and Golgi organization. TAp73 is also required for the asymmetric membrane localization of PCP core proteins Vangl2, Prickle2 and Fzd3 (Fuertes-Alvarez et al, 2018). Interestingly, ciliary axonemes in TAp73KO ECs appear less disheveled than in p73KO counterparts.…”
Section: Dual Role Of P73 In Ependymal Cellsmentioning
confidence: 98%
“…Thus, p73 is required for ependymal maturation and neurogenic SVZ cytoarchitecture (Fujitani et al, 2017;Gonzalez-Cano et al, 2016). TAp73KO ECs exhibit the same PCP and basalbody anchoring defects, identifying TAp73 as the regulator of PCP (Fuertes-Alvarez et al, 2018). Mechanistically, TAp73 regulates translational PCP (asymmetrical polarization of cilia clusters at the anterior apical surface) by directly inducing transcription of Mlck kinase (also known as Mylk), which modulates non-muscle myosin-II activity, thereby affecting the dynamics of actin and microtubulebased transport and Golgi organization.…”
Section: Dual Role Of P73 In Ependymal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Тар73 является важным регулятором и координатором вращательных и поступательных движений ресничек и, таким образом, участвует в прямой циркуляции ликвора. Указанный механизм реализуется посредством модуляции взаимодействия актина и белков микротрубочек с мембранными белками, участвующими в обеспечении полярности клеток и движения ресничек [12].…”
Section: Review Articles фундаментальная и клиническая медицина ®unclassified